Composite positive electrode material suitable for sulfide solid-state lithium battery as well as preparation method and application of composite positive electrode material

Through the liquid solid dispersing-qi solid reaction method, the sulfurization modification of the positive active substances to form a stable sulfide interface phase, solve the problem of chemical side reactions and space charge layers in the interface in the lithium of sulfide solid lithium batteries, significantly improved the electrochemical performance Essence

CN119381446AActive Publication Date: 2025-01-28QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411498553.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In the prior art, when developing composite positive electrode materials suitable for sulfide solid lithium batteries, it is difficult to effectively suppress the interface chemical side reaction between the positive electrode active substance and the sulfide electrolyte and the problem of space charge layer, resulting in limited electrochemical performance.

Method used

The use of liquid solid dispersing-qi-solid reaction method The sulfurization modification of positive active substances to form a stable sulfide interface phase, including the interface buffer layer of the TM-S and SOXN-components, inhibit the chemical reactions of the interface and reduce the space charge layer Influence.

Benefits of technology

Through the uniform sulfide covering layer, the interface chemical side reaction of the positive active substance and sulfide electrolyte is significantly suppressed, reducing the adverse effects of space charge layers on electrochemical performance, promoting the rapid transmission of lithium ions, increasing the sulfide solid -state lithium battery Electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381446A_ABST
    Figure CN119381446A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a composite positive electrode material suitable for a sulfide solid-state lithium battery as well as a preparation method and application thereof. The invention relates to a sulfuration-modified positive electrode active material, which is characterized in that the sulfuration-modified positive electrode active material is modified by a sulfur source through liquid-solid dispersion-gas-solid reaction, so that a layer of sulfide interface phase with a stable structure is constructed on the surface of positive electrode active material particles; and the sulfur source accounts for 0.1-15% of the mass fraction of the positive active material. According to the invention, a liquid-solid dispersion-gas-solid reaction mode is adopted to obtain the sulfurized and modified positive electrode active material, uniform mixing of a sulfur source and the positive electrode active material and uniform sulfurization modification of the positive electrode active material can be realized, and a sulfide interface phase with a stable structure can be constructed. And meanwhile, the preparation method is simple in process and environment-friendly, and batch preparation of the high-performance composite positive electrode material is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and specifically relates to a composite positive electrode material suitable for sulfide solid-state lithium batteries, a preparation method and an application thereof. Background Art

[0002] Sulfide solid-state lithium batteries have the potential advantages of high energy density and high safety, and are one of the development routes of advanced energy storage technology. It should be pointed out that the composite positive electrode material composed of positive electrode active material, sulfide electrolyte and conductive agent is the determining factor affecting the electrochemical performance of sulfide solid-state batteries. In addition to the physical contact state between the components in the composite positive electrode material, such as dispersion degree, contact mode, contact area, gap size, etc., which will affect the ion transfer kinetics and active material utilization rate at the positive electrode active material / sulfide electrolyte interface and affect the electrochemical performance of sulfide solid-state lithium batteries, the interfacial chemical side reactions and space charge layers between the positive electrode active material and the sulfide electrolyte in the composite positive electrode material will also lead to an increase in the impedance of the positive electrode active material / sulfide electrolyte interface, hindering ion interface transmission and limiting the electrochemical performance of sulfide solid-state lithium batteries. Therefore, it is urgent to develop relevant response strategies to solve the interfacial chemical reactions and space charge layer problems faced by positive electrode active materials / sulfide electrolytes.

[0003] CN116230860A discloses a sulfur-based solid electrolyte oxide positive electrode material and its preparation method and application. By adopting a low-speed mechanical ball milling coating process, a conductive oxide material coating layer is constructed on the outside of the oxide positive electrode particles, which effectively prevents the lattice oxygen from escaping from the oxide positive electrode particles and the interfacial chemical side reaction between the oxide positive electrode particles and the sulfur-based solid electrolyte. However, the low-speed mechanical ball milling coating process adopted cannot achieve a uniform and dense thin layer coating of the conductive oxide material on the oxide positive electrode particles, resulting in the existence of an interfacial chemical side reaction between the exposed positive electrode active material and the sulfur-based solid electrolyte. In addition, there is still a large chemical potential difference between the conductive oxide coating material and the sulfur-based solid electrolyte, resulting in the problem of the space charge layer between the oxide positive electrode particles and the sulfur-based solid electrolyte is still relatively prominent.

[0004] Wu et al. (Advanced Functional Materials, 2024, 34, 4, 2309822) used ruthenium oxide to treat lithium-rich manganese-based positive electrode materials (Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 ) is doped with bulk ruthenium, and carbon disulfide vapor is used as the sulfur source to dope Li 1.2 Ni 0.13 Co 0.13 Mn 0.54O 2 Sulfur modification was carried out to form a sulfide surface layer on the surface of the lithium-rich manganese-based positive electrode material, which effectively inhibited the interfacial side reactions between the positive electrode active material and the sulfide electrolyte and the adverse effects of the space charge layer on the ion interface transmission. However, carbon disulfide solution is highly volatile, flammable and explosive, and there are safety risks. In addition, there is the disadvantage of introducing carbon impurities when using carbon disulfide to sulfurize and modify lithium-rich manganese-based positive electrode materials.

[0005] CN111697208B discloses a modified positive electrode material for lithium-ion batteries and a preparation method thereof. The positive electrode material for lithium-ion batteries is subjected to a sulfurization modification treatment under heating conditions using disulfide, trisulfide, cyclohexasulfide, etc. as sulfur sources and utilizing the sublimation characteristics of solid sulfur. The cycle performance and rate performance of the positive electrode material in liquid lithium-ion batteries are effectively improved, and a reference is provided for the preparation of high-performance sulfide solid-state lithium battery composite positive electrode materials. However, the method still has the problem that the sulfurization degree of the positive electrode material for lithium-ion batteries near the elemental sulfur is high and the sulfurization degree of the positive electrode material for lithium-ion batteries far away from the elemental sulfur is low, that is, the sulfurization degree of the positive electrode material for lithium-ion batteries is uneven.

[0006] CN115477335 A discloses a method for preparing a sulfur-modified cobalt-free lithium-rich positive electrode material, wherein an anhydrous ethanol solution of elemental sulfur is added to an aqueous solution of a Ni source and a Mn source, and an aqueous solution of a carbonate is used as a precipitant, and a cobalt-free lithium-rich positive electrode material modified by elemental sulfur doping and sulfate surface coating is obtained by hydrothermal reaction and high-temperature solid phase reaction, which can effectively improve the cycle stability and rate performance of the cobalt-free lithium-rich positive electrode material, but the addition of anhydrous ethanol solution of elemental sulfur in the preparation method will change the coordination environment and solubility product constant of Ni and Mn ions in the aqueous solution, resulting in the problem of uneven distribution of Ni and Mn and element enrichment in local areas in the cobalt-free lithium-rich positive electrode material. Therefore, there is an urgent need for a composite positive electrode material and a preparation method thereof that can not only inhibit the chemical reaction of the positive electrode active material / sulfide electrolyte interface, reduce the adverse effects of the space charge layer, and have simple operation and can significantly improve the electrochemical performance of the sulfide solid-state lithium battery composite positive electrode material. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a composite positive electrode material suitable for sulfide solid-state lithium batteries and a preparation method and application thereof.

[0008] To achieve the above purpose, the present invention adopts the following technical solution:

[0009] A sulfurized positive electrode active material is modified by a sulfur source through liquid-solid dispersion-gas-solid reaction to modify the positive electrode active material so that a layer of sulfide interface phase with stable structure is constructed on the surface of the positive electrode active material particles; the mass fraction of the sulfur source in the positive electrode active material is 0.1%-15%.

[0010] An application of the sulfurized modified positive electrode active material, wherein the sulfurized modified positive electrode active material is used in preparing a composite positive electrode material suitable for a sulfide solid-state lithium battery.

[0011] A composite positive electrode material suitable for a sulfide solid-state lithium battery. The composite positive electrode material comprises the sulfurized modified positive electrode active material, the sulfide electrolyte and the conductive agent in a mass ratio of 30-90:10-70:0.1-5.

[0012] The sulfur-modified positive electrode active material is prepared by dissolving sulfur in an organic alcohol, adding the positive electrode active material after the dissolution to form a uniformly dispersed suspension, and then drying to obtain a solid powder material; the solid powder material is heated at 100-400° C. under vacuum and sealed conditions to sublimate the sulfur, uniformly sulfurize the positive electrode active material, and construct a layer of sulfide interface phase with a stable structure on the surface of the positive electrode active material particles; wherein the sulfide interface phase is a sulfide phase containing TM-S, SO x n- The interface buffer layer comprises components (TM is a transition metal element (generally Ni, Co, Mn) in the positive electrode active material; 3≤x≤4, 0<n≤2); the mass fraction of the sulfur element in the positive electrode active material is 0.1%-15%.

[0013] The organic alcohol is one or more of methanol, ethanol, propanol, propylene glycol, and butanol, and the sulfur element is one or more of disulfide, trisulfide, tetrasulfide, pentasulfide, cyclohexasulfide, and cyclooctasulfide.

[0014] The positive electrode active material is stirred in an organic alcohol solution containing elemental sulfur at room temperature for 0.5-5 hours to obtain a uniformly dispersed suspension, and then vacuum dried at 40-80° C. for 5-24 hours to obtain a solid powder material.

[0015] The positive electrode active material is a positive electrode active material with a high specific capacity, wherein the specific capacity is generally greater than or equal to 180 mAh / g);

[0016] The conductive agent is one or more of conductive carbon black (SP), carbon nanotubes, vapor grown carbon fiber (VGCF) and graphene;

[0017] Sulfide solid electrolyte for Li 6 PS 5 Cl, Li 3 PS 4 , Li 6 PS 5 Br, Li 10 G 2 S 12One or more of .

[0018] The positive electrode active material with high specific capacity is lithium cobalt oxide (LiCoO 2 ), lithium nickel cobalt manganese oxide (LiNi a Co b Mn 1-a-b O 2 ,0.6≤a<1,0<b≤0.2) and lithium-rich manganese-based layered oxides (xLi 2 MnO 3 ·(1-x)LiNi a Co b Mn 1-a-b O 2 , 0<x<1, 0.3≤a<1, 0.3≤b<1) or more.

[0019] A method for preparing a composite positive electrode material suitable for a sulfide solid-state lithium battery comprises the following steps: performing dry ball milling mixing treatment on a sulfurized positive electrode active material, a sulfide electrolyte, and a conductive agent in proportion as described above, so as to achieve sufficient contact and dispersion between the components, and obtain a composite positive electrode material for a sulfide solid-state lithium battery.

[0020] The dry ball milling treatment is carried out in the ball mill, the speed of the ball mill is 100-400 rpm, and the ball milling time is 0.5-5h.

[0021] An application of a composite positive electrode material suitable for a sulfide solid-state lithium battery, and an application of the composite positive electrode material suitable for a sulfide solid-state lithium battery in the preparation of a sulfide electrolyte all-solid-state battery.

[0022] A sulfide electrolyte all-solid-state battery contains the composite positive electrode material.

[0023] The negative electrode of the sulfide electrolyte all-solid-state battery is one of a lithium metal negative electrode, a lithium-indium negative electrode, a carbon negative electrode, a silicon negative electrode, and a silicon-carbon negative electrode.

[0024] Preparation of sulfide electrolyte all-solid-state battery: First, place the sulfide solid electrolyte powder material in a solid-state battery mold and apply pressure to form a sulfide electrolyte layer, then place the composite positive electrode material obtained above on the sulfide solid electrolyte layer from one side of the positive electrode and apply pressure, then place the negative electrode material on the other side of the sulfide solid electrolyte layer and apply pressure. Finally, the preparation of the sulfide electrolyte solid-state battery is completed by sealing rubber rings and pressure mechanical fixtures.

[0025] The advantages of the present invention are:

[0026] The present invention adopts the liquid-solid dispersion-gas-solid reaction method to obtain the sulfurized positive active material, which can achieve uniform mixing of the sulfur source and the positive active material and uniform sulfurization modification of the positive active material, which is conducive to building a sulfide interface phase with stable structure, inhibiting the interface chemical side reaction between the positive active material and the sulfide electrolyte, reducing the adverse effect of the space charge layer on the electrochemical performance of the sulfide solid lithium battery, promoting the efficient transmission of lithium ions at the interface, and helping to improve the electrochemical performance of the sulfide solid lithium battery. At the same time, the preparation method is simple in process, environmentally friendly, and easy to achieve batch preparation of high-performance composite positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of sulfurization modification of positive electrode active materials; wherein, (a) a schematic diagram of sulfurization modification of positive electrode active materials using liquid-solid dispersion-gas-solid reaction method in Example 1; (b) a schematic diagram of sulfurization modification of positive electrode active materials using gas-solid reaction method in Comparative Example 2.

[0028] Figure 2 These are the SEM and EDS images of the sulfurized modified lithium-rich manganese-based positive electrode material in Example 1.

[0029] Figure 3 (a) XPS and (b) XRD patterns of the sulfurized modified lithium-rich manganese-based positive electrode material in Example 1.

[0030] Figure 4 This is the first cycle charge and discharge curve of the sulfide solid-state battery assembled with the composite positive electrode material prepared in Example 1.

[0031] Figure 5 The cycle performance test of the sulfide solid-state battery assembled with the composite positive electrode materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0032] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0033] The present invention utilizes liquid-solid dispersion-gas-solid reaction to carry out sulfurization modification on the positive electrode active material, and realizes uniform sulfurization modification treatment on the positive electrode active material under the coordination of various substances in the positive electrode material, the dosage of elemental sulfur and corresponding conditions, so that a specific uniform and dense layer containing TM-S, SO x n-The sulfide coating layer of the component can inhibit the interfacial chemical side reactions between the positive electrode active material particles and the sulfide electrolyte and effectively eliminate the adverse effects of the space charge layer, reduce the impedance of lithium ions at the positive electrode active material / sulfide electrolyte interface, and promote the rapid transmission of lithium ions. In addition, the sulfurization modification of the positive electrode active material can also achieve the regulation of the surface interface oxygen vacancies, crystal structure, etc. of the positive electrode material, and improve the structural stability and kinetic properties of the positive electrode active material. Therefore, the sulfurized composite positive electrode material has an outstanding advantage of excellent electrochemical performance in sulfide solid-state lithium batteries.

[0034] Example 1

[0035] The composite cathode material for sulfide solid-state batteries is a sulfurized modified lithium-rich manganese-based single crystal cathode material (0.5Li 2 MnO 3 0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 )、Li 6 PS 5 Cl sulfide electrolyte and conductive agent VGCF, including 0.5Li 2 MnO 3 0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Cathode material, Li 6 PS 5 The mass ratio of Cl sulfide electrolyte and conductive agent VGCF is 40:60:3.

[0036] The sulfurization modification method of the composite positive electrode material for sulfide solid-state lithium battery comprises the following specific steps:

[0037] Step 1: 0.03 g of cyclooctasulfide (S 8 ) was added to 300 ml of ethanol solution and stirred magnetically at 30 °C for 1 hour to promote S 8 Completely dissolved in ethanol solution to obtain S 8 of ethanol solution.

[0038] Step 2: 3.0g 0.5Li 2 MnO 3 0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 The positive electrode material is added with the above S 8 The mixture was stirred in an ethanol solution at 30 °C for 2 h to obtain a solid-liquid mixture of a lithium-rich manganese-based cathode and cyclooctasulfur.

[0039] Step 3: The obtained solid-liquid mixture of the lithium-rich manganese-based positive electrode and cyclooctasulfur is transferred to a vacuum oven and vacuum dried at 50° C. for 10 hours to obtain a solid powder material in which the lithium-rich manganese-based positive electrode and cyclooctasulfur are uniformly mixed.

[0040] Step 4: Place the powder obtained in the above step in a quartz glass tube and perform vacuum sealing treatment, such as Figure 1 As shown in a. The sealed quartz glass tube was placed in a muffle furnace and heated to 200°C at a heating rate of 2°C / min and maintained for 12 hours. The sulfurized modified lithium-rich manganese-based positive electrode material (see Figure 2 and 3 ).

[0041] like Figure 2 and 3 The following are the scanning electron micrographs and energy dispersive X-ray spectroscopy analysis of the sulfurized lithium-rich manganese-based cathode material. After sulfurization, the surface of the lithium-rich manganese-based cathode material contains TM-S and SO x n- The sulfide interface phase of the components, powder X-ray diffraction analysis shows that the lithium-rich manganese-based positive electrode material still maintains a good layered crystal structure after sulfurization modification treatment.

[0042] Preparation method of composite positive electrode material suitable for sulfide solid-state lithium battery: In a glove box filled with argon, 2g of sulfurized modified lithium-rich manganese-based positive electrode material and 3g of sulfide electrolyte Li 6 PS 5 Cl, 0.15g of conductive agent VGCF were placed in a ball mill, and 20 zirconia ball milling beads with a diameter of 10mm were placed. The ball milling was carried out at a speed of 250rpm for 2 hours to obtain a sulfurized composite positive electrode material. The obtained composite positive electrode material was then manually ground in a glove box for 0.5 hours to obtain a lithium-rich manganese-based single crystal positive electrode material, Li 6 PS 5 Composite cathode material with full contact and mixing of Cl and VGCF components.

[0043] Sulfide electrolyte all-solid-state battery: Sulfide solid-state batteries are assembled in a glove box filled with argon. The all-solid-state battery is assembled using a STC-SB polyetheretherketone (PEEK) finished mold with a diameter of 10 mm. First, 80 mg of LPSCl powder is added to the column cavity and pressed at 150 MPa for 2 min. Then, 10 mg of composite positive electrode powder is evenly spread on one side of the electrolyte sheet and pressed at 370 MPa for 2 min. Finally, a lithium-indium alloy negative electrode composed of indium foil (Φ=8 mm) and lithium foil (Φ=3 mm) is placed on the other side of the electrolyte sheet and pressed at 150 MPa for 1 min. At this time, a three-layer structure of positive electrode-electrolyte-negative electrode is formed inside the battery, and current collector sheets are respectively installed at both ends of the positive and negative electrodes to promote carrier transfer. During the electrochemical test, a stainless steel press is installed on the outside of the battery mold to stabilize the contact of the internal components of the battery by applying strong external pressure. The electrochemical test was carried out at 30 ° C, 2.0-4.7V (vs.Li + / Li)、0.1C(1C=200mAg -1 ) under the conditions.

[0044] Comparative Example 1

[0045] The composite cathode material for sulfide solid-state batteries is composed of lithium-rich manganese-based single crystal cathode material (0.5Li 2 MnO 3 0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 )、Li 6 PS 5 Cl sulfide electrolyte and conductive agent VGCF, among which lithium-rich manganese-based single crystal positive electrode material, Li 6 PS 5 The mass ratio of Cl sulfide electrolyte and conductive agent VGCF is 40:60:3.

[0046] The specific steps of lithium-rich manganese-based single crystal positive electrode material are:

[0047] Step 1: Add 3.0 g of lithium-rich manganese-based single crystal positive electrode material into 300 ml of ethanol solution, and magnetically stir at 30° C. for 2 hours to obtain a suspension of lithium-rich manganese-based single crystal positive electrode material.

[0048] Step 2: Transfer the obtained suspension of lithium-rich manganese-based single crystal positive electrode material into a vacuum oven, and vacuum dry it at 50° C. for 10 hours to obtain a solid powder of the lithium-rich manganese-based single crystal positive electrode material.

[0049] Step 3: Place the solid powder of the lithium-rich manganese-based single crystal positive electrode material in a quartz glass tube and perform vacuum sealing treatment, place the sealed quartz glass tube in a muffle furnace, heat it to 200°C at a heating rate of 2°C / min and maintain it for 12 hours to obtain a lithium-rich manganese-based single crystal positive electrode material.

[0050] Preparation method of composite positive electrode material for sulfide solid-state battery: In a glove box filled with argon, 2g of lithium-rich manganese-based single crystal positive electrode material and 3g of sulfide electrolyte Li 6 PS 5 Cl, 0.15g of conductive agent VGCF were placed in a ball mill, and 20 zirconia ball milling beads with a diameter of 10mm were placed. The ball milling was carried out at a speed of 250rpm for 2 hours to obtain a lithium-rich manganese-based composite positive electrode material, Li 6 PS 5 Composite cathode material with full contact and mixing of Cl and VGCF components.

[0051] Assemble the sulfide solid-state battery according to Example 1: Assemble the obtained lithium-rich manganese-based sulfide composite positive electrode, Li 6 PS 5 The Cl sulfide electrolyte and lithium-indium alloy negative electrode material were assembled into a sulfide solid-state battery in a glove box filled with argon.

[0052] The sulfide solid-state batteries assembled in Example 1 and Comparative Example 1 were respectively heated at 30°C and 2.0-4.7V (vs. Li + / Li)、0.1C(1C=200mAg -1 ) conditions for charge and discharge test (participate in Figure 4 and 5 ).

[0053] like Figure 4 and 5 As shown in the figure, the sulfide solid-state lithium battery assembled in Example 1 has a first-cycle discharge capacity of 175.24 mAh g -1 The first cycle coulomb efficiency is 73.44%, and the discharge capacity of the solid-state lithium battery still reaches 177.40 mAh g after 100 cycles. -1 The sulfide solid-state lithium battery assembled in Comparative Example 1 has a first-cycle discharge capacity of only 76.13 mAh g -1 The first cycle coulomb efficiency is 59.63%, and the discharge capacity of the solid-state lithium battery after 100 cycles is only 110.06 mAh g -1It can be seen from the two that the positive electrode material obtained in Example 1 is modified by sulfurization of the positive electrode active material particles through liquid-solid dispersion-gas-solid reaction, which overcomes the shortcomings of the previous technology in the process of sulfurization of the positive electrode active material, such as the introduction of additional pollution sources and uneven sulfurization degree, and can form a uniform and dense layer containing TM-S, SO on the surface of the positive electrode active material particles. x n- The sulfide coating layer of the component can inhibit the interfacial chemical side reaction between the positive electrode active material particles and the sulfide electrolyte and effectively eliminate the adverse effects of the space charge layer, reduce the impedance of lithium ions at the positive electrode active material / sulfide electrolyte interface, and promote the rapid transmission of lithium ions. It can be seen that the battery assembled in comparative example 1 significantly inhibits the chemical decomposition of the sulfide electrolyte during charging and discharging, reduces electrochemical polarization, and promotes the rapid transmission of lithium ions, so it has higher capacity contribution and coulomb efficiency. Compared with the sulfide solid-state lithium batteries based on lithium-rich manganese-based positive electrode materials reported at home and abroad, this performance is at the leading level.

[0054] Example 2

[0055] Sulfide solid-state battery composite cathode material is sulfur modified lithium-rich manganese-based single crystal cathode material, Li 6 PS 5 Cl sulfide electrolyte and conductive agent VGCF, among which, sulfurized modified lithium-rich manganese-based single crystal positive electrode material, Li 6 PS 5 The mass ratio of Cl sulfide electrolyte and conductive agent VGCF is 40:60:3.

[0056] The sulfurization modification method of the composite positive electrode material for sulfide solid-state lithium battery comprises the following specific steps:

[0057] Step 1: 0.015 g of cyclooctasulfide (S 8 ) was added to 300 ml of ethanol solution and stirred magnetically at 30 °C for 1 hour to promote S 8 Completely dissolved in ethanol solution to obtain S 8 of ethanol solution.

[0058] Step 2: 3.0g lithium-rich manganese-based single crystal positive electrode material (0.5Li 2 MnO 3 0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ) Add the above S 8 The mixture was stirred in an ethanol solution at 30 °C for 2 h to obtain a solid-liquid mixture of a lithium-rich manganese-based cathode and cyclooctasulfur.

[0059] Step 3: Transfer the obtained solid-liquid mixture of lithium-rich manganese-based positive electrode and cyclooctasulfur into a vacuum oven, and vacuum dry it at 50° C. for 10 hours to obtain a solid powder material in which the lithium-rich manganese-based single crystal positive electrode and cyclooctasulfur are uniformly mixed.

[0060] Step 4: Place the uniformly mixed lithium-rich manganese-based single crystal positive electrode and cyclooctasulfur solid powder material in a quartz glass tube and perform vacuum sealing treatment, place the sealed quartz glass tube in a muffle furnace, heat it to 200°C at a heating rate of 2°C / min, and maintain it for 12 hours to obtain a sulfurized lithium-rich manganese-based single crystal positive electrode material.

[0061] Preparation method of composite positive electrode material suitable for sulfide solid-state lithium battery: in a glove box filled with argon, 2g of the sulfurized lithium-rich manganese-based single crystal positive electrode material obtained above, 3g of sulfide electrolyte Li 6 PS 5 Cl, 0.15g of conductive agent VGCF were placed in a ball mill, and 20 zirconia ball milling beads with a diameter of 10mm were placed. The ball milling was carried out at a speed of 250rpm for 2 hours to obtain a sulfurized composite positive electrode material. The obtained composite positive electrode material was then manually ground in a glove box for 0.5 hours to obtain a lithium-rich manganese-based single crystal positive electrode material, Li 6 PS 5 Composite cathode material with full contact and mixing of Cl and VGCF components.

[0062] Sulfide solid-state batteries were assembled according to Example 1 and heated at 30°C and 2.0-4.7V (vs. Li + / Li)、0.1C(1C=200mAg -1 ) conditions. The assembled sulfide solid-state lithium battery has a first-cycle discharge capacity of 168.3 mAh g -1 , the first-cycle Coulomb efficiency is 72.2%.

[0063] Example 3

[0064] Sulfide solid-state battery composite cathode material is sulfur modified lithium-rich manganese-based single crystal cathode material, Li 6 PS 5 Cl sulfide electrolyte and conductive agent VGCF, among which, sulfurized modified lithium-rich manganese-based single crystal positive electrode material, Li 6 PS 5 The mass ratio of Cl sulfide electrolyte and conductive agent VGCF is 40:60:3.

[0065] The sulfurization modification method of the composite positive electrode material for sulfide solid-state lithium battery comprises the following specific steps:

[0066] Step 1: 0.045 g of cyclooctasulfide (S 8) was added to 300 ml of ethanol solution and stirred magnetically at 30 °C for 1 hour to promote S 8 Completely dissolved in ethanol solution to obtain S 8 of ethanol solution.

[0067] Step 2: 3.0g lithium-rich manganese-based single crystal positive electrode material (0.5Li 2 MnO 3 0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ) Add the above S 8 The mixture was stirred in an ethanol solution at 30°C for 2 hours to obtain a solid-liquid mixture of lithium-rich manganese-based single crystal positive electrode material and cyclooctasulfur.

[0068] Step 3: Transfer the obtained solid-liquid mixture of lithium-rich manganese-based single crystal positive electrode material and cyclooctasulfur into a vacuum oven, and vacuum dry it at 50°C for 10 hours to obtain a solid powder material in which the lithium-rich manganese-based single crystal positive electrode material and cyclooctasulfur are fully dispersed and mixed.

[0069] Step 4: Place the fully dispersed and mixed lithium-rich manganese-based single crystal positive electrode material and cyclooctasulfur solid powder material in a quartz glass tube and perform vacuum sealing treatment, place the sealed quartz glass tube in a muffle furnace, heat it to 220°C at a heating rate of 2°C / min, and maintain it for 8 hours to obtain a sulfurized lithium-rich manganese-based single crystal positive electrode material.

[0070] Preparation method of composite positive electrode material suitable for sulfide solid-state lithium battery: In a glove box filled with argon, 2g of sulfurized modified lithium-rich manganese-based single crystal positive electrode material and 3g of sulfide electrolyte Li 6 PS 5 Cl, 0.15g of conductive agent VGCF were placed in a ball mill, and 20 zirconia ball milling beads with a diameter of 10mm were placed. The ball milling was carried out at a speed of 200rpm for 3 hours to obtain a sulfurized composite positive electrode material. The obtained composite positive electrode material was then manually ground in a glove box for 0.5 hours to obtain a lithium-rich manganese-based single crystal positive electrode material, Li 6 PS 5 Composite cathode material with full contact and mixing of Cl and VGCF components.

[0071] Sulfide solid-state batteries were assembled according to Example 1 and heated at 30°C and 2.0-4.7V (vs. Li + / Li)、0.1C(1C=200mAg -1 ) conditions. The assembled sulfide solid-state lithium battery has a first-cycle discharge capacity of 170.0 mAh g -1, the first-cycle Coulomb efficiency is 74.1%.

[0072] Example 4

[0073] The composite cathode material for sulfide solid-state batteries is a sulfurized modified lithium cobalt oxide cathode material (LiCoO 2 )、Li 10 G 2 S 12 Sulfide electrolyte and conductive agent SP, wherein the sulfurized modified lithium cobalt oxide positive electrode material, Li 10 G 2 S 12 The mass ratio of the sulfide electrolyte to the conductive agent SP is 70:30:3.

[0074] The sulfurization modification method of the composite positive electrode material for sulfide solid-state lithium battery comprises the following specific steps:

[0075] Step 1: 0.03 g of cyclooctasulfide (S 8 ) was added to 300 ml of ethanol solution and stirred magnetically at 30 °C for 1 hour to promote S 8 Completely dissolved in ethanol solution to obtain S 8 of ethanol solution.

[0076] Step 2: Add 3.0g of lithium cobalt oxide positive electrode material to the above S 8 The mixture was stirred in an ethanol solution at 30°C for 2 hours to obtain a solid-liquid mixture of lithium cobalt oxide positive electrode material and cyclooctasulfide.

[0077] Step 3: Transfer the obtained solid-liquid mixture of lithium cobalt oxide positive electrode material and cyclooctasulfide into a vacuum oven, and vacuum dry it at 55° C. for 12 hours to obtain a solid powder material in which the lithium cobalt oxide positive electrode material and cyclooctasulfide are fully dispersed and mixed.

[0078] Step 4: Place the fully dispersed and mixed lithium cobalt oxide positive electrode material and cyclooctasulfur solid powder material in a quartz glass tube and perform vacuum sealing treatment, place the sealed quartz glass tube in a muffle furnace, heat it to 190°C at a heating rate of 2°C / min, and maintain it for 20 hours to obtain a sulfurized lithium cobalt oxide positive electrode material.

[0079] Preparation method of composite positive electrode material suitable for sulfide solid-state lithium battery: In a glove box filled with argon, 2.1g of sulfurized lithium cobalt oxide positive electrode material, 0.9g of sulfide electrolyte Li 10 G 2 S 12, 0.09g of conductive agent SP was placed in a ball mill, and 20 zirconia ball milling beads with a diameter of 10mm were placed, and the ball milling was carried out at a speed of 200rpm for 5 hours to obtain a sulfurized composite positive electrode material. The obtained composite positive electrode material was then manually ground in a glove box for 0.5 hours to obtain a lithium cobalt oxide positive electrode material, Li 10 G 2 S 12 A composite positive electrode material that is fully in contact with and mixed with the SP component.

[0080] The sulfide solid-state battery was assembled according to Example 1 and heated at 30°C, 2.5-4.2V (vs. Li + / Li)、0.1C(1C=140mAg -1 ) conditions. The assembled sulfide solid-state lithium battery has a first-cycle discharge capacity of 115.0 mAh g -1 , the first-cycle Coulomb efficiency is 86.7%.

[0081] Example 5

[0082] The composite cathode material for sulfide solid-state batteries is a sulfurized modified lithium cobalt oxide cathode material (LiCoO 2 )、Li 6 PS 5 Cl sulfide electrolyte and conductive agent VGCF, among which, sulfurized modified lithium cobalt oxide positive electrode material, Li 6 PS 5 The mass ratio of Cl sulfide electrolyte and conductive agent VGCF is 70:30:3.

[0083] The sulfurization modification method of the composite positive electrode material for sulfide solid-state lithium battery comprises the following specific steps:

[0084] Step 1: 0.045 g disulfide (S 2 ) was added to 300 ml of propylene glycol solution and stirred magnetically at 30 ° C for 1 hour to promote S 2 Completely dissolved in propylene glycol solution to obtain S 2 of propylene glycol solution.

[0085] Step 2: Add 3.0g of lithium cobalt oxide positive electrode material to the above S 2 The mixture was stirred in a propylene glycol solution at 30° C. for 2 hours to obtain a solid-liquid mixture of lithium cobalt oxide positive electrode material and disulfide.

[0086] Step 3: Transfer the obtained solid-liquid mixture of lithium cobalt oxide positive electrode material and disulfide into a vacuum oven, and vacuum dry it at 55° C. for 12 hours to obtain a solid powder material in which the lithium cobalt oxide positive electrode material and disulfide are fully dispersed and mixed.

[0087] Step 4: Place the fully dispersed and mixed lithium cobalt oxide positive electrode material and disulfide solid powder material in a quartz glass tube and perform vacuum sealing treatment, place the sealed quartz glass tube in a muffle furnace, heat it to 190°C at a heating rate of 2°C / min, and maintain it for 20 hours to obtain a sulfurized lithium cobalt oxide positive electrode material.

[0088] Preparation method of composite positive electrode material suitable for sulfide solid-state lithium battery: In a glove box filled with argon, 2.1g of sulfurized lithium cobalt oxide positive electrode material, 0.9g of sulfide electrolyte Li 6 PS 5 Cl, 0.09g of conductive agent VGCF were placed in a ball mill, and 20 zirconia ball milling beads with a diameter of 10mm were placed. The ball milling was carried out at a speed of 200rpm for 5 hours to obtain a sulfurized composite positive electrode material. The obtained composite positive electrode material was then manually ground in a glove box for 0.5 hours to obtain a nickel cobalt manganese oxide positive electrode material, Li 6 PS 5 Composite cathode material with full contact and mixing of Cl and SP components.

[0089] Sulfide solid-state batteries were assembled according to Example 1 and tested at 30°C, 2.5-4.2V (vs. Li + / Li)、0.1C(1C=140mAg -1 ) conditions. The assembled sulfide solid-state lithium battery has a first-cycle discharge capacity of 111.0 mAh g -1 , the first-cycle Coulomb efficiency is 83.6%.

[0090] Example 6

[0091] The composite cathode material for sulfide solid-state batteries is a sulfurized modified lithium nickel cobalt manganese oxide cathode material (LiNi 0.8 Co 0.1 Mn 0.1 O 2 )、Li 6 PS 5 Cl sulfide electrolyte and conductive agent VGCF, among which, sulfurized modified nickel cobalt manganese oxide lithium positive electrode material, Li 6 PS 5 The mass ratio of Cl sulfide electrolyte and conductive agent VGCF is 70:30:3.

[0092] The sulfurization modification method of the composite positive electrode material for sulfide solid-state lithium battery comprises the following specific steps:

[0093] Step 1: 0.015 g of cyclooctasulfide (S 8 ) was added to 300 ml of propylene glycol solution and stirred magnetically at 30 ° C for 1 hour to promote S 8Completely dissolved in propylene glycol solution to obtain S 8 of propylene glycol solution.

[0094] Step 2: Add 3.0g of lithium nickel cobalt manganese oxide positive electrode material to the above S 8 The mixture was stirred in a propylene glycol solution at 30° C. for 2 hours to obtain a solid-liquid mixture of nickel cobalt manganese oxide positive electrode material and cyclooctasulfide.

[0095] Step 3: Transfer the obtained solid-liquid mixture of the nickel cobalt manganese oxide positive electrode material and cyclooctasulfide into a vacuum oven, and vacuum dry it at 55° C. for 12 hours to obtain a solid powder material in which the nickel cobalt manganese oxide positive electrode material and cyclooctasulfide are fully dispersed and mixed.

[0096] Step 4: Place the fully dispersed and mixed nickel cobalt manganese oxide lithium positive electrode material and cyclooctasulfur solid powder material in a quartz glass tube and perform vacuum sealing treatment, place the sealed quartz glass tube in a muffle furnace, heat it to 200°C at a heating rate of 2°C / min, and maintain it for 20 hours to obtain a sulfurized nickel cobalt manganese oxide lithium positive electrode material.

[0097] Preparation method of composite positive electrode material suitable for sulfide solid-state lithium battery: In a glove box filled with argon, 2.1g of sulfurized nickel cobalt manganese oxide positive electrode material, 0.9g of sulfide electrolyte Li 6 PS 5 Cl, 0.09g of conductive agent VGCF were placed in a ball mill, and 20 zirconia ball milling beads with a diameter of 10mm were placed. The ball milling was carried out at a speed of 200rpm for 5 hours to obtain a sulfurized composite positive electrode material. The obtained composite positive electrode material was then manually ground in a glove box for 0.5 hours to obtain a nickel cobalt manganese oxide positive electrode material, Li 6 PS 5 Composite cathode material with full contact and mixing of Cl and VGCF components.

[0098] Sulfide solid-state batteries were assembled as described in Example 1 and charged at 30°C, 3.0-4.3V (vs. Li + / Li)、0.1C(1C=200mAg -1 ) conditions. The assembled sulfide solid-state lithium battery has a first-cycle discharge capacity of 143.1 mAh g -1 , the first-cycle Coulomb efficiency is 82.2%.

[0099] Comparative Example 2

[0100] Sulfide solid-state battery composite cathode material is sulfur modified lithium-rich manganese-based single crystal cathode material, Li 6 PS 5Cl sulfide electrolyte and conductive agent VGCF, among which, sulfurized modified lithium-rich manganese-based single crystal positive electrode material, Li 6 PS 5 The mass ratio of Cl sulfide electrolyte and conductive agent VGCF is 40:60:3.

[0101] Sulfide solid-state lithium battery composite positive electrode material, the specific steps are:

[0102] Step 1: 0.03 g of cyclooctasulfide (S 2 ) is placed in a quartz tube 1, and 3.0 g of lithium-rich manganese-based single crystal positive electrode material (0.5Li 2 MnO 3 0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ) is placed in a quartz tube 2, such as Figure 1 As shown in b.

[0103] Step 2: The quartz glass tube 2 is vacuum sealed and placed in a muffle furnace, and the temperature is raised to 200° C. at a heating rate of 2° C. / min and maintained for 12 hours to obtain a sulfurized modified lithium-rich manganese-based positive electrode material.

[0104] Step 3: In a glove box filled with argon, 2 g of sulfurized lithium-rich manganese-based cathode material and 3 g of sulfide electrolyte Li 6 PS 5 Cl and 0.15 g of conductive agent VGCF were placed in a ball mill jar, and 20 zirconia ball mill beads with a diameter of 10 mm were placed. The jar was ball milled at a rotation speed of 250 rpm for 2 hours to obtain a sulfurized composite positive electrode material.

[0105] The obtained composite cathode material was then manually ground in a glove box for 0.5 hours to obtain a lithium-rich manganese-based cathode material, Li 6 PS 5 Composite cathode material with full contact and mixing of Cl and VGCF components.

[0106] Sulfide solid-state battery: The sulfur-modified lithium-rich manganese-based sulfide composite positive electrode, Li 6 PS 5 The Cl sulfide electrolyte and lithium-indium alloy negative electrode material were assembled into a sulfide solid-state battery in a glove box filled with argon.

[0107] The assembled sulfide solid-state battery was heated at 30°C and 2.0-4.7V (vs. Li + / Li)、0.1C(1C=200mAg -1The charge and discharge test was carried out under the condition of 200 mAh / s. The first cycle discharge capacity of the assembled sulfide solid lithium battery was 110.51 mAh g -1 The first cycle coulomb efficiency is 68.82%, and the discharge capacity of the solid-state lithium battery after 100 cycles is 121.06 mAh g -1 . Compared with the battery assembled with positive electrode active materials using liquid-solid dispersion-gas-solid reaction in the present invention, although a sulfide coating layer is formed, the degree of sulfurization of the lithium-rich manganese-based single crystal positive electrode material by elemental S in Comparative Example 2 is uneven, resulting in the sulfide coating layer not being evenly coated on the surface of the positive electrode material. The embodiment of the present invention can use elemental S to uniformly sulfurize the positive electrode material, and the formed sulfurized coating layer can be evenly coated on the surface of the positive electrode material, inhibiting the interfacial chemical side reactions between the positive electrode active material particles and the sulfide electrolyte and eliminating the adverse effects of the space charge layer, reducing the impedance of lithium ions at the positive electrode active material / sulfide electrolyte interface, and promoting the rapid transmission of lithium ions. In addition, the sulfurization modification treatment of the positive electrode active material can also achieve the regulation of the surface oxygen vacancies, crystal structure, etc. of the positive electrode material, and improve the structural stability and kinetic properties of the positive electrode active material.

[0108] See Table 1 for a comparison of the composite positive electrode material composition and electrochemical performance of the above embodiments and comparative examples.

[0109] Table 1

[0110]

Claims

1. A sulfurized positive electrode active material, characterized in that: The sulfurized positive electrode active material is modified by a sulfur source through liquid-solid dispersion-gas-solid reaction, so that a layer of structurally stable sulfide interface phase is constructed on the surface of the positive electrode active material particles; the mass fraction of the sulfur source in the positive electrode active material is 0.1%-15%.

2. An application of the sulfurized positive electrode active material according to claim 1, characterized in that: The sulfurized modified positive electrode active material is used in the preparation of a composite positive electrode material suitable for a sulfide solid-state lithium battery.

3. A composite positive electrode material suitable for sulfide solid-state lithium batteries, characterized in that: The composite positive electrode material is in a mass ratio of 30-90:10-70: 0.1-5 of the sulfurized positive electrode active material according to claim 1, a sulfide electrolyte and a conductive agent.

4. The composite positive electrode material suitable for sulfide solid-state lithium battery according to claim 3, characterized in that: The sulfur-modified positive electrode active material is prepared by dissolving sulfur in an organic alcohol, adding the positive electrode active material after the dissolution to uniformly disperse the suspension, and then drying to obtain a solid powder material; the solid powder material is vacuum-sealed and heated at 100-400° C. to sublime the sulfur, uniformly sulfurize the positive electrode active material, and construct a layer of sulfide interface phase with a stable structure on the surface of the positive electrode active material particles; the mass fraction of the sulfur in the positive electrode active material is 0.1%-15%.

5. The composite positive electrode material suitable for sulfide solid-state lithium battery according to claim 4, characterized in that: The organic alcohol is one or more of methanol, ethanol, propanol, propylene glycol, and butanol; the sulfur element is one or more of disulfide, trisulfide, tetrasulfide, pentasulfide, cyclohexasulfide, and cyclooctasulfide.

6. The composite positive electrode material suitable for sulfide solid-state lithium battery according to claim 4, characterized in that: The positive electrode active material is stirred in an organic alcohol solution containing elemental sulfur at room temperature for 0.5-5 hours to obtain a uniformly dispersed suspension, and then vacuum dried at 40-80° C. for 5-24 hours to obtain a solid powder material.

7. The composite positive electrode material suitable for sulfide solid-state lithium battery according to claim 3 or 4, characterized in that: The positive electrode active material is a positive electrode active material with high specific capacity; The conductive agent is one or more of conductive carbon black (SP), carbon nanotubes (carbon nanotubes), vapor grown carbon fiber (VGCF) and graphene (Graphene); Sulfide solid electrolytes are Li6PS5Cl, Li3PS4, Li6PS5Br, Li 10 GeP2S 12 One or more of .

8. A method for preparing a composite positive electrode material suitable for a sulfide solid-state lithium battery according to claim 3, characterized in that: According to the above description, the sulfurized positive electrode active material, sulfide electrolyte and conductive agent described in claim 1 are dry-milled and mixed in proportion to achieve full contact and dispersion between the components to obtain a composite positive electrode material for a sulfide solid-state lithium battery.

9. An application of the composite positive electrode material suitable for sulfide solid-state lithium battery according to claim 3, characterized in that: The composite positive electrode material suitable for sulfide solid-state lithium battery is used in the preparation of sulfide electrolyte all-solid-state battery.

10. A sulfide electrolyte all-solid-state battery, characterized in that: Containing the composite positive electrode material according to claim 3.

Citation Information

Patent Citations

  • Modified lithium ion battery positive electrode material and preparation method thereof

    CN111697208B

  • Preparation method for coating anode material of lithium battery

    CN103579590A

  • Composite positive electrode material for sulfide solid-state battery as well as preparation method and application of composite positive electrode material

    CN117410463A

  • Electrode material based on transition metal sulfide and preparation and application thereof

    CN118472240A